More than three billion people globally are eating too much or too little. But we can fix our faulty food system - Hirvonen, Kalle; Headey, Derek D.; Masters, William A.; Bai, Yan (2019)
Messages around healthy eating are nothing new – but nowadays we are increasingly told to eat well not just for our own health but also for the planet. This debate was given a boost at the beginning of 2019 with the publication of the EAT-Lancet Commission on the world's diet, which called for a “great food transformation”. It condemned the world’s "faulty food system" which sees nearly one billion people go hungry, almost two billion eat too much of the wrong type of food, and which puts unsustainable pressure on the planet.